An analysis of infiltration in initial gradient soils - SONI , J. P.; BASAK, P. (MAUSAM, 1979)
Flow through loamy and clay soils starts only when the hydraulic gradients exceeds a certain value called initial gradient, thus giving rise to non-Darcian flow. An analytical solution of the problem of infiltration into homogeneous soil with initial gradient has been presented, which shall be quite useful in the area-of irrigation and drainage. The effect of initial gradient on the advance of wetting front, the infiltration rate and accumulated depth of infiltration has been clearly brought out, and it is found that the non-recognition of initial gradient in sqils leads to the overestimation of these values.